Estimation of Serum Aldosterone and Electrolytes in Pregnancy Induced Hypertension - A.H.Jasim, Shaimaa; M.Sulaiman, Shakir (Tikrit Journal of Pharmaceutical Sciences, 2023)
Pregnancy Induced Hypertension(PIH) is one of the most frequent complications of pregnancy , however little is known about its etiology. The renin angiotensin aldosterone system(RAAS) has been implicated in the pathogenesis of PIH. The study of serum electrolytes is gaining ground in the pathophysiology of hypertension. The study sample consist of 50 normal non pregnant women, 50 normotensive pregnant women, and 50 preeclamptic pregnant women in their third trimester in Mosul city. The aim of this study was designed to evaluate the role of serum aldosterone and the serum electrolytes in pathogenesis of PIH. The results of this study showed that there was a highly significant reduction (P<0.000) in serum sodium, calcium, and aldosterone levels in preeclamptic pregnant women in comparison with normotensive pregnant women & the control group. While there is a highly significant elevation (P<0.000) in the serum level of potassium in preeclamptic women in comparison with normotensive pregnant women & the control group. The serum chloride level showed a highly significant reduction (P<0.006) in preeclamptic women in comparison with the normotensive pregnant women. The serum aldosterone has a positive and negative correlation with serum sodium and potassium respectively in preeclamptic pregnant women